Fluorine doping for improved thermoelectric properties of spark plasma sintered bismuth telluride - Kim, Jinseo; Duy, Le Thai; Kang, Hyunwoo; Ahn, Byungmin; Seo, Hyungtak (Journal of Materials Science and Technology, 2021)
Bismuth-telluride (Bi2Te3) is considered to have the best thermoelectric properties at room temperature (ca. 300 K). Thus, synthesis and improvement of Bi2Te3 and its derivatives quickly and cost-effectively at favorite temperatures are of interests. Recently, doping fluorine (F) into electronic materials (e.g., FTO) has gained attention; however, it is not applied to Bi2Te3 till now. Here, our synthesis of F-doped Bi2Te3 for thermoelectric application is introduced using spark plasma sintering (SPS) for Bi2Te3 preparation and reactive ion etching (RIE, with SF6 gas) for F-doping. The exposure time of SF6 plasma is adjusted to evaluate F-doping effect on the thermoelectric properties of the samples. During characterizations, the increased electrical conductivity and the improved Seebeck coefficient of F-doped Bi2Te3 are observed. Through spectroscopic studies and DFT calculations, the main mechanism behind that improvement is unveiled. It also emphasizes the essential role of the F-doping (optimum treatment time of 40 s) in increasing the carrier concentrations as well as electrical conductivity. With increasing measurement temperature (300–510 K), F-doping raises the figure of merit of electron rich Bi2Te3 from 1.0 to 1.11 (peaked at 390 K).
Keywords: Bismuth telluride; Electrical conductivity; Electronic materials; Figure of merits; Measurement temperatures; Spectroscopic studies; Thermoelectric application; Thermoelectric properties; Bismuth-telluride; Doping; Fluorine; Spark plasma sintering; Thermoelectric